Super-hydrophilic separation membrane, and preparation method and application thereof
Patent Information
- Application Number
- CN202610746394.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-05-28
AI Technical Summary
现有技术中,单宁酸改性多集中于基膜表面原位沉积或铸膜液直接共混,存在羟基基团暴露不足、络合结构不稳定、亲水性提升效果有限、长期使用易流失等问题
[0015]与现有技术相比,本申请的有益效果至少包括:1)本申请超亲水分离膜的亲水性和渗透通量提升显著:未改性膜表面水接触角多在67.4°~79.4°,经本申请改性后,膜表面水接触角可降至37.5°~52.8°,膜亲水性大幅优化。在油水分离过程中,改性后膜的渗透通量由569.4 Lm-2h-1bar-1提升至862.2 Lm-2h-1bar-1。
Smart Images

Figure CN122252034B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of functional polymer membrane materials technology, and in particular to a superhydrophilic separation membrane, its preparation method and application. Background Technology
[0002] Membrane separation technology, with its advantages of low energy consumption, high separation efficiency, and no secondary pollution, has been widely used in many fields such as water treatment, biomedicine, and food processing. Among them, the phase inversion method is the most commonly used industrial method for preparing polymer separation membranes. Commonly used substrates such as polyvinylidene fluoride (PVDF), polysulfone (PSF), polyethersulfone (PES), and polyacrylonitrile (PAN) have advantages such as good chemical stability, high mechanical strength, and resistance to acid and alkali corrosion. However, they generally have defects such as low surface energy and poor intrinsic hydrophilicity. During the separation process, they are prone to adsorbing pollutants, causing membrane fouling, which leads to rapid decline in membrane flux, shortened service life, and a significant increase in operating costs, seriously limiting their application efficiency. Currently, methods for improving membrane hydrophilicity mainly include blending modification, surface coating, and surface graft polymerization. Traditional blending modification often involves directly adding hydrophilic inorganic particles or polymeric additives, but this can easily lead to problems such as uneven dispersion of additives, poor compatibility with the substrate resulting in phase separation, increased membrane structural defects, and decreased mechanical properties. Furthermore, hydrophilic additives are prone to loss into the coagulation bath during phase transformation, resulting in limited surface hydrophilization effects. Surface coating is relatively simple to operate, but the coating layer is mostly bonded to the base membrane through physical action, resulting in poor stability and easy detachment under water erosion. While surface graft polymerization can obtain stable covalently bonded hydrophilic layers, the process is relatively complex, some systems require the use of organic solvents or toxic monomers, and equipment costs are high, making large-scale production difficult.
[0003] Tannic acid is a widely available, biodegradable, non-toxic, and harmless natural plant polyphenol. Its molecular structure is rich in hydrophilic hydroxyl groups such as catechol and pyrogallol, possessing both excellent metal ion complexing ability and substrate adhesion, making it an ideal hydrophilic modifier for membranes. In existing technologies, tannic acid modification mainly focuses on in-situ deposition on the substrate surface or direct blending with the casting solution, which suffers from problems such as insufficient exposure of hydroxyl groups, unstable complex structures, limited hydrophilicity enhancement, and easy loss over long-term use. Summary of the Invention
[0004] This application provides a superhydrophilic separation membrane, its preparation method, and its application, in order to at least solve one of the technical problems existing in the prior art.
[0005] In a first aspect, this application provides a method for preparing a superhydrophilic separation membrane, comprising the following steps: Polyvinylidene fluoride, pore-forming agent, and organic solvent are mixed, heated and stirred, and allowed to stand to remove bubbles to obtain casting solution; Prepare an aqueous solution of tannic acid, wherein the mass concentration of the aqueous solution of tannic acid is 0.1~0.5 wt%. The casting solution is scraped onto a support plate and then immersed in the tannic acid aqueous solution to undergo phase inversion and obtain a tannic acid pre-modified membrane. The tannic acid pre-modified membrane was completely immersed in an aqueous solution of metal ions, then removed and rinsed to obtain the superhydrophilic separation membrane; the concentration of the aqueous solution of metal ions was 10~40 mmol / L.
[0006] In one embodiment, the mass concentration of the tannic acid aqueous solution is 0.1~0.3wt%.
[0007] In one embodiment, the mass concentration of the tannic acid aqueous solution is 0.1 wt%.
[0008] In one embodiment, the concentration of the aqueous solution of metal ions is 10 mmol / L.
[0009] In one embodiment, the aqueous solution of metal ions is at least one of divalent copper ions, trivalent iron ions, and tetravalent zirconium ions.
[0010] In one embodiment, based on the casting solution by mass of 100%, the polyvinylidene fluoride by mass fraction is 12-20%, the pore-forming agent by mass fraction is 2-8%, and the balance is the organic solvent.
[0011] In one embodiment, the pore-forming agent is polyvinylpyrrolidone; The organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.
[0012] In one embodiment, the phase transformation requires a temperature of 25-35°C and a time of 5-30 minutes.
[0013] Secondly, this application provides a superhydrophilic separation membrane, which is prepared by the above-described preparation method.
[0014] Thirdly, this application provides the application of superhydrophilic separation membranes in oil-water separation.
[0015] Compared with the prior art, the beneficial effects of this application include at least the following: 1) The hydrophilicity and permeate flux of the superhydrophilic separation membrane of this application are significantly improved: the water contact angle on the surface of the unmodified membrane is mostly between 67.4° and 79.4°, while after modification by this application, the water contact angle on the membrane surface can be reduced to 37.5° to 52.8°, and the hydrophilicity of the membrane is greatly optimized. In the oil-water separation process, the permeate flux of the modified membrane increases from 569.4 Lm -2 h -1bar -1 Increased to 862.2 Lm -2 h -1 bar -1 .
[0016] 2) The process of this application is mild and environmentally friendly: water is used as the solvent throughout the process, and there is no need for high temperature and high pressure, toxic monomers and organic solvents. The operation is simple and the conditions are mild, making it suitable for industrial continuous production.
[0017] 3) This application employs a reaction surface segregation strategy of 'phase transformation followed by metal coordination', utilizing the spontaneous migration behavior of the polyphenolic hydroxyl groups of tannic acid during the phase transformation process to achieve interfacial enrichment. After membrane formation, coordination crosslinking is achieved through post-metal ion treatment, ultimately forming a structurally stable metal-polyphenol network on the membrane surface. The interfacial enrichment of the metal-polyphenol network in this application endows the membrane surface with more hydrophilic sites, a structural feature that cannot be achieved through blending.
[0018] It should be understood that the description in this section is not intended to identify key or essential features of the embodiments of this disclosure, nor is it intended to limit the scope of this disclosure. Other features of this disclosure will become readily apparent from the following description. Attached Figure Description
[0019] The above and other objects, features, and advantages of this disclosure will become readily apparent from the following detailed description of exemplary embodiments, taken in conjunction with the accompanying drawings. Several embodiments of this disclosure are illustrated in the drawings by way of example and not limitation, in which: In the accompanying drawings, the same or corresponding reference numerals indicate the same or corresponding parts.
[0020] Figure 1 A scanning electron microscope image of the superhydrophilic separation membrane of Embodiment 1 of this disclosure is shown; Figure 2 A scanning electron microscope image of the separation membrane of Comparative Example 1 of this disclosure is shown; Figure 3 The surface water contact angle diagrams of the separation membranes prepared according to embodiments and comparative examples of this disclosure are shown; Figure 4 The membrane permeation flux diagrams of the separation membranes prepared according to the embodiments and comparative examples of this disclosure are shown. Detailed Implementation
[0021] To make the objectives, features, and advantages of this disclosure more apparent and understandable, the technical solutions in the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this disclosure, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without creative effort are within the scope of protection of this disclosure.
[0022] To address the shortcomings of existing technologies, this application proposes to introduce tannic acid into a coagulation bath to participate in phase transformation and membrane formation. Then, through post-treatment with a metal ion solution, a stable hydrophilic polyphenol-metal network structure is constructed on the membrane surface and surface pore walls by utilizing the coordination and chelation effect of tannic acid and metal ions. This significantly improves the hydrophilicity of the membrane surface, optimizes the membrane pore structure, enhances the membrane's antifouling performance, and compensates for the deficiencies of existing modification processes.
[0023] Therefore, in a first aspect, this application provides a method for preparing a superhydrophilic separation membrane, comprising the following steps: Step 1) Mix polyvinylidene fluoride, pore-forming agent, and organic solvent, heat and stir, and let stand to remove bubbles to obtain casting solution; Step 2), prepare an aqueous solution of tannic acid as a coagulation bath, the mass concentration of which is 0.1~0.5wt%; Step 3) The casting solution is scraped onto the support plate and then immersed in an aqueous solution of tannic acid to carry out phase inversion and obtain a tannic acid pre-modified membrane. Step 4): The tannic acid pre-modified membrane is completely immersed in the metal ion aqueous solution and the coordination chelation reaction is carried out at room temperature. After the reaction is completed, the membrane is removed and thoroughly rinsed with deionized water to obtain a superhydrophilic separation membrane. The concentration of the metal ion aqueous solution is 10~40 mmol / L.
[0024] This application adds tannic acid to the coagulation bath. During the phase inversion and membrane formation process, the polymer solution and the coagulation bath undergo dual diffusion. Tannic acid molecules are simultaneously adsorbed and deposited on the membrane surface and surface pore walls along with solvent exchange, achieving initial hydrophilic modification using hydroxyl groups. During subsequent metal ion post-treatment, the catechol and pyrogallol groups in the tannic acid molecules undergo rapid coordination chelation reactions with metal ions, forming a cross-linked metal-polyphenol network structure on the membrane surface. This network structure is rich in a large number of uncoordinated hydrophilic hydroxyl groups, which significantly improves the stability of the modified layer, prevents tannic acid loss, and thus persistently enhances the hydrophilicity of the membrane surface. At the same time, the coordination cross-linking process can moderately control the membrane pore size, optimize the membrane flux and retention performance, and enhance the membrane surface's antifouling ability.
[0025] For example, in step 2), the mass concentration of the tannic acid aqueous solution is 0.1~0.3wt%. Exemplarily, the mass concentration of the tannic acid aqueous solution is 0.1wt%, 0.2wt%, or 0.3wt%. Preferably, the mass concentration of the tannic acid aqueous solution is 0.1wt%.
[0026] For example, in step 4), the concentration of the metal ion aqueous solution is 10 mmol / L (i.e., 10 mM), 20 mmol / L, 30 mmol / L, or 40 mmol / L. Preferably, the concentration of the metal ion aqueous solution is 10 mmol / L.
[0027] For example, the aqueous solution of metal ions is at least one of divalent copper ion aqueous solution, trivalent iron ion aqueous solution, and tetravalent zirconium ion aqueous solution.
[0028] For example, in step 1), based on the casting solution mass of 100%, the mass fraction of polyvinylidene fluoride is 12-20%, the mass fraction of the porogen is 2-8%, and the balance is an organic solvent. Exemplarily, the mass fraction of polyvinylidene fluoride is 12%, 14%, 16%, 18%, or 20%. Exemplarily, the mass fraction of the porogen is 2%, 4%, 6%, or 8%.
[0029] For example, the porogen is polyvinylpyrrolidone; the organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide. Preferably, the organic solvent is N,N-dimethylacetamide.
[0030] For example, in step 3), the temperature required for the phase transformation is 25~35℃, and the time is 5~30min. In step 3), the support plate is made of glass.
[0031] For example, in step 4), the tannic acid pre-modified membrane is completely immersed in an aqueous solution of metal ions and soaked at room temperature for 5-60 minutes.
[0032] Secondly, this application provides a superhydrophilic separation membrane, which is prepared by the above-described method. The superhydrophilic separation membrane prepared in this application can be applied to oil-water separation. The superhydrophilicity and permeate flux of the superhydrophilic separation membrane of this application are significantly improved: the water contact angle on the surface of the unmodified membrane is mostly between 67.4° and 79.4°, while after modification in this application, the water contact angle on the membrane surface can be reduced to 37.5° to 52.8°, indicating a significant optimization of hydrophilicity. During the oil-water separation process, the permeate flux of the modified membrane increases from 569.4 Lm. -2 h -1 bar -1 Increased to 862.2 Lm -2 h -1 bar -1 .
[0033] The present application will be further described in detail below with reference to the embodiments.
[0034] Example 1 A method for preparing a superhydrophilic separation membrane includes the following steps: 8g of polyvinylidene fluoride, 3g of polyvinylpyrrolidone, and 39g of N,N Dimethylacetamide was added to a round-bottom flask and heated and stirred in an oil bath at 60°C for 6 hours. Then, the mixture was allowed to stand for 12 hours to remove bubbles, thus obtaining the casting solution.
[0035] After the casting solution was cooled to room temperature, it was poured onto a glass plate and scraped into a liquid film of about 200 μm thickness. The film was then placed in a 0.1 wt% tannic acid coagulation bath at 25°C and solidified for 5 minutes. After being removed from the glass plate, the film was soaked in deionized water for 24 hours to obtain a tannic acid pre-modified film.
[0036] The tannic acid pre-modified membrane was completely immersed in a 10 mM ferric nitrate aqueous solution and soaked at room temperature for 30 min to carry out a coordination chelation reaction. After the reaction was completed, the membrane was removed, thoroughly rinsed with deionized water, and dried to obtain a superhydrophilic separation membrane (denoted as superhydrophilic separation membrane 1).
[0037] The superhydrophilic separation membrane 1 prepared in Example 1 was analyzed by electron microscopy, and the results are as follows: Figure 1 As shown, from Figure 1 As can be seen, the membrane surface exhibits a porous structure. Furthermore, the pure water flux of the membrane in Example 1 is 1634.1 Lm. -2 h -1 bar -1 In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 862.2 Lm -2 h -1 bar -1 The rejection rate was 99.5%. The wettability of water droplets on the membrane surface was observed using a contact angle meter. A 2 μL water droplet was applied to the membrane surface, and the initial contact angle was 37.5°. Figure 3 As shown.
[0038] Among them, pure water flux is used to measure the initial water permeability of the hydrophilic membrane. The higher the pure water flux value, the better the water flux performance of the membrane.
[0039] Permeation flux measures the amount of fluid passing through a unit membrane area per unit time under unit pressure; the higher the permeation flux value, the stronger the membrane's permeation performance.
[0040] The rejection rate reflects the membrane's ability to retain target substances; a higher rejection rate indicates a better membrane separation effect.
[0041] The contact angle is used to characterize the wettability of the membrane surface; the smaller the contact angle, the stronger the hydrophilicity.
[0042] Example 2 The preparation process of the superhydrophilic separation membrane in Example 2 is basically the same as that in Example 1, except that the concentration of the ferric nitrate aqueous solution is 30 mM.
[0043] In Example 2, a superhydrophilic separation membrane (denoted as superhydrophilic separation membrane 2) was prepared.
[0044] Electron microscopy analysis of the superhydrophilic separation membrane 2 in Example 2 revealed a porous structure on its surface, with a pure water flux of 1577.6 Lm. -2 h -1 bar -1 In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 811.7 Lm -2 h -1 bar -1 The rejection rate was 99.6%. The wettability of water droplets on the membrane surface was observed using a contact angle meter. When a 2 μL water droplet was applied to the membrane surface, the initial contact angle was 52.8°. Figure 3 As shown.
[0045] Example 3 The preparation process of the superhydrophilic separation membrane in Example 3 is basically the same as that in Example 1, except that the mass concentration of the tannic acid aqueous solution is 0.3 wt%, and a tannic acid pre-modified membrane is obtained. The tannic acid pre-modified membrane is completely immersed in a 10 mM ferric nitrate aqueous solution and soaked at room temperature for 30 min to carry out a coordination chelation reaction. After the reaction is completed, it is taken out, thoroughly rinsed with deionized water, and dried to obtain the superhydrophilic separation membrane (denoted as superhydrophilic separation membrane 3).
[0046] Electron microscopy analysis of the superhydrophilic separation membrane 3 from Example 3 revealed a porous structure on the membrane surface, with a pure water flux of 1152 Lm. -2 h -1 bar -1 In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 738 Lm -2 h -1 bar -1The rejection rate was 100%. The wettability of water droplets on the membrane surface was observed using a contact angle meter. A 2μL water droplet was applied to the membrane surface, and the initial contact angle of the droplet on the membrane surface was 40.5°. Figure 3 As shown.
[0047] Example 4 The preparation process of the superhydrophilic separation membrane in Example 4 is basically the same as that in Example 1, except that the mass concentration of the tannic acid aqueous solution is 0.5 wt%, and a tannic acid pre-modified membrane is obtained. The tannic acid pre-modified membrane is completely immersed in a 10 mM ferric nitrate aqueous solution and soaked at room temperature for 30 min to carry out a coordination chelation reaction. After the reaction is completed, it is taken out, thoroughly rinsed with deionized water, and dried to obtain the separation membrane (denoted as superhydrophilic separation membrane 4).
[0048] Electron microscopy analysis of the superhydrophilic separation membrane 4 in Example 4 revealed a porous structure on the membrane surface, with a pure water flux of 1066 Lm. -2 h -1 bar -1 In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 720 Lm -2 h -1 bar -1 The rejection rate was 100%. The wettability of water droplets on the membrane surface was observed using a contact angle meter. A 2 μL water droplet was applied to the membrane surface, and the initial contact angle was 42.3°. Figure 3 As shown.
[0049] Comparative Example 1 The preparation of Comparative Example 1 was basically the same as that of Example 1, except that Comparative Example 1 used deionized water as a coagulation bath and did not involve coordination chelation reaction with aqueous metal ion solution.
[0050] Specifically, the preparation process of the polyvinylidene fluoride membrane in Comparative Example 1 is as follows: 8g of polyvinylidene fluoride, 3g of polyvinylpyrrolidone, and 39g of N,N Dimethylacetamide was added to a round-bottom flask and heated and stirred in an oil bath at 60°C for 6 hours. Then, the mixture was allowed to stand for 12 hours to remove bubbles, thus obtaining the casting solution. After cooling the casting solution to room temperature, it was poured onto a glass plate and scraped into a liquid film of about 200 μm thickness. The film was then placed in a coagulation bath of deionized water at 25°C and allowed to solidify for 5 minutes. After being removed from the glass plate, the film was soaked in deionized water for 24 hours to obtain a polyvinylidene fluoride membrane (denoted as separation membrane 1).
[0051] The separation membrane 1 of Comparative Example 1 was analyzed by electron microscopy, and the results are as follows: Figure 2 As shown, from Figure 2As can be seen, the membrane surface exhibits a porous structure. The membrane's pure water flux is 1543.9 Lm. -2 h -1 bar -1 In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 569.4 Lm. -2 h -1 bar -1 The rejection rate was 99.1%. The wettability of water droplets on the membrane surface was observed using a contact angle meter. When a 2 μL water droplet was applied to the membrane surface, the initial contact angle was 79.4°. Figure 3 As shown.
[0052] Comparative Example 2 The preparation process of the polyvinylidene fluoride membrane in Comparative Example 2 is as follows: The preparation process of the polyvinylidene fluoride membrane in Comparative Example 2 is basically the same as that in Comparative Example 1, except that the deionized water coagulation bath is replaced with a 0.1wt% tannic acid coagulation bath to obtain the polyvinylidene fluoride membrane (denoted as separation membrane 2).
[0053] Electron microscopy analysis of the separation membrane 2 in Comparative Example 2 revealed a porous structure on its surface, with a pure water flux of 1592.9 Lm. -2 h -1 bar -1 In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 784 Lm -2 h -1 bar -1 The rejection rate was 99.2%. The wettability of water droplets on the membrane surface was observed using a contact angle meter. When a 2 μL water droplet was applied to the membrane surface, the initial contact angle was 67.4°. Figure 3 As shown.
[0054] Comparative Example 3 The preparation process of the separation membrane in Comparative Example 3 is basically the same as that in Example 1, except that the concentration of the ferric nitrate aqueous solution is 50 mM.
[0055] In Comparative Example 3, a separation membrane was prepared (denoted as separation membrane 3).
[0056] Electron microscopy analysis of the separation membrane 3 in Comparative Example 3 revealed a porous structure on its surface, with a pure water flux of 1548.5 Lm. -2 h -1 bar -1In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 776.6 Lm -2 h -1 bar -1 The rejection rate was 100%. The wettability of the water droplet on the membrane surface was observed using a contact angle meter. A 2μL water droplet was applied to the membrane surface, and the initial contact angle of the water droplet on the membrane surface was 71.3°. Figure 3 As shown.
[0057] Comparative Example 4 The preparation process of the polyvinylidene fluoride membrane in Comparative Example 4 was basically the same as that in Comparative Example 1, except that tannic acid was added to the casting solution, with a mass fraction of 0.1%, to obtain the polyvinylidene fluoride membrane (denoted as separation membrane 4). Specifically, 8g of polyvinylidene fluoride, 3g of polyvinylpyrrolidone, 0.05g of tannic acid, and 38.95g of N,N Dimethylacetamide was added to a round-bottom flask and heated and stirred in an oil bath at 60°C for 6 hours. Then, the mixture was allowed to stand for 12 hours to remove bubbles, thus obtaining the casting solution. After cooling the casting solution to room temperature, it was poured onto a glass plate and scraped into a liquid film of about 200 μm thickness. The film was then placed in a coagulation bath of deionized water at 25°C and allowed to solidify for 5 minutes. After being removed from the glass plate, the film was soaked in deionized water for 24 hours to obtain a polyvinylidene fluoride membrane (denoted as separation membrane 4).
[0058] Electron microscopy analysis of the separation membrane 4 in Comparative Example 4 revealed a porous structure on its surface, with a pure water flux of 1545.9 Lm. -2 h -1 bar -1 In the application of oil-water emulsion separation (0.1 wt% pump oil, 0.01 wt% SDS, 99.89 wt% water), membrane permeation flux data can be found in [reference needed]. Figure 4 Its value is 582 Lm -2 h -1 bar -1 The rejection rate was 99.1%. The wettability of water droplets on the membrane surface was observed using a contact angle meter. When a 2 μL water droplet was applied to the membrane surface, the initial contact angle was 76.2°. Figure 3 As shown.
[0059] A comparison of the membrane pure water flux, membrane permeate flux, rejection rate, and initial contact angle data of Examples 1-2 and Comparative Example 1 shows that the superhydrophilic separation membranes prepared in Examples 1-2 are superior to those in Comparative Example 1 in both pure water flux and permeate flux. Example 1, in particular, achieves optimal results in all three aspects simultaneously. While the separation membrane in Comparative Example 1 has a slightly higher pure water flux, its permeate flux is low, and its initial contact angle is as high as 79.4°, indicating poor hydrophilicity.
[0060] The comparison between Comparative Example 2 and Example 1 shows that if the tannic acid pre-modified membrane is not immersed in the metal ion aqueous solution for coordination chelation reaction, the initial contact angle of the resulting separation membrane will increase significantly, and the hydrophilicity of the membrane will deteriorate.
[0061] The comparison between Comparative Example 3 and Example 1 shows that if the concentration of the metal ion aqueous solution (ferric nitrate aqueous solution) is greater than 40 mM, the pure water flux and permeation flux of the prepared separation membrane are reduced, and the initial contact angle is increased. This indicates that the separation membrane's permeability, permeability, and hydrophilicity are all deteriorated.
[0062] A comparison of Examples 1 and 3-4 shows that, under the same conditions, when the mass concentration of the tannic acid aqueous solution increases from 0.1 wt% to 0.5 wt%, both the membrane pure water flux and the membrane permeate flux of the superhydrophilic separation membrane decrease, especially the membrane pure water flux, which decreases from 1634.1 Lm. -2 h -1 bar -1 Reduced to 1066 Lm -2 h -1 bar -1 This indicates that the mass concentration of tannic acid aqueous solution has a significant impact on the performance of superhydrophilic separation membranes.
[0063] Comparing Comparative Example 4 with Comparative Example 2, it can be seen that, under the same conditions, adding tannic acid directly to the casting solution significantly reduces the permeate flux and hydrophilicity of the prepared separation membrane. The membrane permeate flux decreased from 784 Lm. -2 h -1 bar -1 Reduced to 582Lm -2 h -1 bar -1 The contact angle increased from 67.4° to 76.2°. This indicates that by using a reaction surface segregation film-forming strategy, the spontaneous migration behavior of tannic acid during phase transformation is utilized to achieve interfacial enrichment, giving the film surface more hydrophilic sites of polyphenolic hydroxyl groups. This structural feature cannot be achieved by the casting solution blending method.
[0064] In summary, compared with existing technologies, this application significantly improves hydrophilicity and permeate flux: the water contact angle of the unmodified membrane surface is mostly between 67.4° and 79.4°, while after modification with this application, the water contact angle of the membrane surface can be reduced to 37.5° to 52.8°, resulting in a substantial optimization of hydrophilicity. During oil-water separation, the permeate flux of the modified membrane increases from 569.4 Lm. -2 h -1 bar -1 Increased to 862.2 Lm -2 h -1 bar -1 The membrane prepared in Example 1 exhibited the best overall performance. Furthermore, the process described in this application is mild and environmentally friendly: it uses water as the solvent throughout, eliminating the need for high temperatures, high pressures, toxic monomers, and organic solvents. The operation is simple, the conditions are mild, and it is suitable for continuous industrial production.
[0065] It should be understood that the various forms of processes shown above can be used to rearrange, add, or delete steps. For example, the steps described in this disclosure can be executed in parallel, sequentially, or in different orders, as long as the desired result of the technical solution of this disclosure can be achieved, and this is not limited herein.
[0066] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this disclosure, "a plurality of" means two or more, unless otherwise explicitly specified.
[0067] The above description is merely a specific embodiment of this disclosure, but the scope of protection of this disclosure is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this disclosure should be included within the scope of protection of this disclosure. Therefore, the scope of protection of this disclosure should be determined by the scope of the claims.
Claims
1. A method for preparing a superhydrophilic separation membrane, characterized in that, Includes the following steps: Polyvinylidene fluoride, a pore-forming agent, and an organic solvent are mixed, heated and stirred, and allowed to stand to remove bubbles to obtain a casting solution; wherein the pore-forming agent is polyvinylpyrrolidone. Prepare an aqueous solution of tannic acid, wherein the mass concentration of the aqueous solution of tannic acid is 0.1~0.3 wt%. The casting solution is coated onto a support plate and then immersed in the tannic acid aqueous solution to undergo phase inversion to obtain a tannic acid pre-modified membrane; the temperature required for the phase inversion is 25~35℃ and the time is 5~30min. The tannic acid pre-modified membrane was completely immersed in an aqueous solution of metal ions, then removed and rinsed to obtain the superhydrophilic separation membrane; the concentration of the aqueous solution of metal ions was 10~40 mmol / L.
2. The preparation method according to claim 1, characterized in that, The mass concentration of the tannic acid aqueous solution is 0.1 wt%.
3. The preparation method according to claim 1, characterized in that, The concentration of the aqueous solution containing the metal ions is 10 mmol / L.
4. The preparation method according to claim 1, characterized in that, The aqueous solution of the metal ions is at least one of divalent copper ion aqueous solution, trivalent iron ion aqueous solution, and tetravalent zirconium ion aqueous solution.
5. The preparation method according to claim 1, characterized in that, Based on the casting solution as 100% by mass, the polyvinylidene fluoride has a mass fraction of 12-20%, the pore-forming agent has a mass fraction of 2-8%, and the balance is the organic solvent.
6. The preparation method according to claim 1, characterized in that, The organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.
7. A superhydrophilic separation membrane, characterized in that, The superhydrophilic separation membrane is prepared by the preparation method according to any one of claims 1-6.
8. The application of the superhydrophilic separation membrane according to claim 7 in oil-water separation.
Citation Information
Patent Citations
Hydrophilic modification method of high-flux PVDF porous membrane
CN109621739A
